RECONSTRUCTING THE CONCEPT OF SUMMARY PROOF WITHIN THE LEGAL FRAMEWORK OF SMALL CLAIMS PROCEDURES - Kresna Ramadhan Wijaya; Rachmi Sulistyarini; M. Natsir Asnawi (PT. Radja Intercontinental Publishing, 2026)
This research analyzes the legal reasoning (ratio legis) behind the qualification of